2014
DOI: 10.1038/nm.3560
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a new therapeutic peptide that depletes myeloid-derived suppressor cells in tumor-bearing mice

Abstract: Cancer immune evasion is an emerging hallmark of disease progression. Functional studies to understand the role of myeloid-derived suppressor cells (MDSC) in the tumor microenvironment however, are limited by the lack of available specific cell surface markers. We adapted a competitive peptide phage display platform to identify candidate peptides binding MDSC specifically and generated peptide-Fc fusion proteins (peptibody). In multiple tumor models peptibody injection iv completely depleted blood, splenic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
168
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(175 citation statements)
references
References 16 publications
4
168
0
Order By: Relevance
“…Figure 1C), which have not been reported in tumors after anti-VEGF therapy. These cells display a high level of CX3CR1, while Ly6C hi monocytes and Ly6G + neutrophils (hereafter referred to as neutrophils) express CCR2 and CXCR2, respectively (25,39,44) (Supplemental Figure 2B).…”
Section: Anti-vegfr2 Therapy Induces Accumulation Of Monocytes and Nementioning
confidence: 99%
“…Figure 1C), which have not been reported in tumors after anti-VEGF therapy. These cells display a high level of CX3CR1, while Ly6C hi monocytes and Ly6G + neutrophils (hereafter referred to as neutrophils) express CCR2 and CXCR2, respectively (25,39,44) (Supplemental Figure 2B).…”
Section: Anti-vegfr2 Therapy Induces Accumulation Of Monocytes and Nementioning
confidence: 99%
“…1 In our recent publication, we demonstrated that MDSC are also present in the tumor microenvironment of mouse lymphomas and exert immunosuppressive and protumoral effects. 2 Taken together, these reports suggest that tumor-associated myeloid cells in B-cell lymphomas exist in different functional states and may collectively promote tumor growth and confer poor prognosis.…”
mentioning
confidence: 92%
“…2 The peptides were further developed into therapeutic agents (peptibodies) that efficiently depleted splenic and intratumoral MDSC in tumor-bearing mice, but did not affect other proinflammatory cell types including dendritic cells, T, B, and NK lymphocytes, and immature myeloid cells in bone marrow, suggesting limited off-target activity. The peptibody treatment was associated with retardation of tumor growth in vivo highlighting the role of MDSC in tumorogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although research in the pathways involved in MDSC formation and maturation is still ongoing and novel potential targets to deplete MDSCs are being identified [126], successes have been obtained via cytokine therapy (local delivery of IL-12 or IFNα) or by the triggering of their TLRs 25 [127]. Once more, CpG ODN-delivering NPs were shown to have potential [122] as well as less known particulate adjuvants, such as very small size proteoliposomes (that combine outer membrane vesicles from N.meningitidis with a GM3 ganglioside) which were shown to modulate myeloid populations within the tumor environment, overcome T cell unresponsiveness and reduce tumor growth [128].…”
mentioning
confidence: 99%